Estratégias de condução de populações segregantes de soja portadoras do gene RR e seleção por meio de análises uni e multivariada - Silva, Fabiana Mota da [UNESP] (2015)
Soybean crop is considered a culture of great economic importance, due to the fact that this crop is the most consumed oilseed in the world. The improvement in the Brazilian soybean production is mostly due to the effort of plant breeding programs. Therefore, the efficiency of selection will depend on the genetic gain and on the breeding methods adopted to conduct the populations on the occasion of progenies evaluation. According to the breeder convenience, some modifications may be made on the traditional methods for conducting the segregating populations. Within this context, the bulk method with selection on F3 is an alternative. Furthermore, the univariate and multivariate techniques of data analyses may improve the soybean breeding progress, due to the possibility to predict the genetic gain and to applicate efficient methodologies which may assist to select promising genotypes. Due to the few numbers of studies that show the efficiency of bulk method with selection in F3, the aim of this study was to evaluate the efficiency of bulk method with selection in F3 in comparison to the traditional bulk method, for traits of agronomic interest in soybean, seeking to compare which conducting strategy is more efficient in terms of genetic gain, as well to select superior families using univariate and multivariate analyses. For conducting the study, 20 segregating populations were used and conducted by two methods, bulk and bulk with selection in F3 (bulkF3), which originated its families in generations F3, F4 and F5.The 60 best families were selected within each method, according to their agronomic performance. The following traits were evaluated: height of the first hull (HFH), plant height at maturity (PHM), number of hulls per plant (NHP), number of branches per plant (NBP), hundred seeds weight (HSW) and grains yield (GY). The two methods were compared by the estimated genetic components, the predicted genetic gain and the predicted ...